1996
DOI: 10.1007/s001250050484
|View full text |Cite
|
Sign up to set email alerts
|

Molecular scanning of the insulin receptor substrate-1 (IRS-1) gene in Japanese patients with NIDDM: identification of five novel polymorphisms

Abstract: Since the insulin receptor substrate-1 (IRS-1) is the major substrate of the insulin receptor tyrosine kinase and has been shown to activate phosphatidylinositol (PI) 3-kinase and promote GLUT4 translocation, the IRS-1 gene is a potential candidate for development of non-insulin-dependent diabetes mellitus (NIDDM). In this study, we have identified IRS-1 gene polymorphisms, evaluated their frequencies in Japanese subjects, and analysed the contribution of these polymorphisms to the development of NIDDM. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Several polymorphisms including a codon 972 mutation of the IRS-1 gene have been reported but their diabetogenic effects are still unclear [4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. In this study we found that the frequency of the codon 972 mutation is 4.6% in type-2 DM patients and 4.9% in healthy control subjects.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Several polymorphisms including a codon 972 mutation of the IRS-1 gene have been reported but their diabetogenic effects are still unclear [4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18]. In this study we found that the frequency of the codon 972 mutation is 4.6% in type-2 DM patients and 4.9% in healthy control subjects.…”
Section: Discussionsupporting
confidence: 49%
“…Concerning insulin sensitivity, it was previously reported that subjects with the mutant allele have low insulin sensitivity compared to subjects without the mutation [17]. Clausen et al [10]reported on a Dannish white man who was homozygous for the mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several amino acid variants in the IRS-1 gene have been identi®ed in humans [31±34]. These include Ala512Pro and Gly971Arg [31], Pro170Arg, Ser809Phe and Met209Thr [32], Ser892Gly [33], and Gly819Arg and Arg1221Cys [34]. With the exception of Gly971Arg, all are rare, and are thus not likely to be major determinants of Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The investigators reported a 40 % reduction in the basal levels and function of IRS -1 protein in the skeletal muscle of patients carrying this variant (Rung, Cauchi et al 2009). Likewise, there are numerous studies in humans demonstrating polymorphisms in the IRS-1 gene associated with variable responsiveness to insulin signaling (Imai, Fusco et al 1994; Ura, Araki et al 1996; Le Fur, Le Stunff et al 2002). The most common polymorphism, the G972R variant, has also been associated with type II diabetes mellitus (Almind, Bjørbaek et al 1993; Sesti 2000; Tok, Ertunc et al 2006).…”
Section: Discussionmentioning
confidence: 99%